The Role of Omega-3 Fatty Acids in Neuroprotection: Molecular Mechanisms and Clinical Implications in Neurodegenerative Diseases. Focus on Alzheimer’s Disease, Multiple Sclerosis and Parkinson’s Disease - Patelski, Mikołaj; Molenda, Jakub; Czapla, Maciej; Surma, Mateusz; Pietrzak, Barbara; Kotlarz, Wiktoria; Kamińska, Marta; Kuczma, Matylda; Mikusek, Wiktoria; Dobrzeniecki , Krzysztof; Klimczak, Adrianna (Quality in Sport, 2025)
Among omega-3 fats, DHA and EPA stand out for their role in keeping the brain and nervous system healthy. Because the body cannot make sufficient amounts by itself, dietary intake is essential. These nutrients help nerve cells remain flexible and support smooth communication in the nervous system. While DHA is especially valuable for memory and mental performance, EPA, on the other hand, is mostly associated with managing brain inflammation. Omega-3s protect nerve cells by easing inflammation and promoting cell survival. They also help damaged nerve tissue heal and encourage the growth of new brain cells, which supports clear thinking and learning. Certain substances derived from DHA and EPA help protect the brain from stress and cell loss. Researchers have found that omega-3s may be useful for people dealing with Alzheimer’s, Parkinson’s and multiple sclerosis. In Alzheimer’s disease, these fats might preserve connections between brain cells. In Parkinson’s disease, they may assist with movement and nerve function. For people with MS, omega-3s could help by lowering inflammation and promoting the repair of nerve fibers. While omega-3s aren’t a cure, including them in the diet might help protect brain health and slow down the progression of the diseases.